2018
DOI: 10.2147/cmar.s176242
|View full text |Cite
|
Sign up to set email alerts
|

Ki-67 index and percentage of sarcomatoid differentiation were two independent prognostic predictors in sarcomatoid renal cell carcinoma

Abstract: PurposeTo identify whether and which of pathological features of sarcomatoid differentiation (SD) in renal cell carcinoma (RCC) can be used as independent predictors associated with overall survival (OS).Materials and methodsAfter institutional review board approval, patients with a diagnosis of sarcomatoid RCC (sRCC), spindled RCC, or RCC with the presence of spindle cells between 2003 and 2017 were further selected and re-examined. The primary pathological features including histological subtypes, tumor necr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Yu et al (26) described 42 patients with RCCs and confirmed that patients with positive immunophenotypes for p53, Bcl‐2, and CAIX had an adverse outcome. Wang et al (27) found that the Ki‐67 index of sarcomatoid differentiation was one of the most important independent predictors, particularly for nonmetastatic RCCs patients. Kawakami et al (10) compared the highly immunosuppressive characteristics between RCCs and an appropriate ccRCC control.…”
Section: Discussionmentioning
confidence: 99%
“…Yu et al (26) described 42 patients with RCCs and confirmed that patients with positive immunophenotypes for p53, Bcl‐2, and CAIX had an adverse outcome. Wang et al (27) found that the Ki‐67 index of sarcomatoid differentiation was one of the most important independent predictors, particularly for nonmetastatic RCCs patients. Kawakami et al (10) compared the highly immunosuppressive characteristics between RCCs and an appropriate ccRCC control.…”
Section: Discussionmentioning
confidence: 99%
“…By far, a number of studies have examined various clinical and pathological variables as prognostic factors in patients with sRCC. Several significant prognostic factors have been found, including T stage, lymph node status, distant metastasis, histology type, percentage of sarcomatoid dedifferentiation, and blood markers (2)(3)(4)(7)(8)(9)(10)(11)(12)(13)(14)(15). Moreover, several prognostic models have been developed to accurately predict tumor prognosis in each patient with sRCC (4, 11,14).…”
Section: Introductionmentioning
confidence: 99%